A new species of Phrynopus (Anura: Craugastoridae) from the central Peruvian Andes - Mamani, Luis; Malqui, Sergio (Zootaxa, 2014)
We describe a new species of Phrynopus from the humid grassland of Distrito de Comas, Provincia Concepcion, Department of Junin. The new species is diagnosed by the lack of dentigerous processes of vomers, tympanic annulus and membrane imperceptible through the skin, males with nuptial pads and vocal slits, warty dorsal skin, and aerolate throat, belly and ventral surfaces of thighs, by possessing pronounced subconical tubercles in the post-tympanic area, by having rounded finger and toe tips with no disc structure, and by its overall dark brown to black coloration with few white and yellow spots in the dorsum and a dark-brown belly with white to gray blotches. Specimens were found under stones at a single area of the central Peruvian Andes at elevations between 4205–4490 m.a.s.l. The eggs had an average diameter of 4.3 mm. With the description and naming of the new species, the genus Phrynopus now contains 26 species, all of them endemic to Peru, and five of which are restricted to Departamento Junin.